Balanced SSFP Transient Imaging using Variable Flip Angles for a Predefined Signal Profile - Worters, Pauline W. (2010)
Variable flip angles are used in steady-state free precession (SSFP) acquisitions (e.g., time-of-flight) but to a lesser extent than in spin echo acquisitions. In balanced SSFP (bSSFP), imaging is often assumed to occur during the steady state, which has been well-described in the literature. However, in many cases, imaging occurs during the transient stage and the use of variable flip angles can improve signal and thus image quality. Here, we present the calculation of flip angles in transient balanced SSFP to generate a predefined signal profile. The signal profile was iteratively optimized to maximize the integral of the signal versus time curve. The key contribution of this work is the formulation of the flip angle as a deterministic function of the preceding and desired magnetization. Catalyzation schemes, e.g., Kaiser-windowed ramp, can be combined with variable flip angles bSSFP to reduce signal oscillations. A uniform signal profile was used as an example to demonstrate the variable flip angle algorithm. Accuracy of the algorithm and Bloch simulations were verified with MRI phantom acquisitions. Renal angiograms were acquired using an inflow-based bSSFP MR angiography technique; improved small vessel depiction was observed in volunteer examinations.